Effectiveness of GeoGebra-Based Interactive Multimedia to Improve Mathematical Concept Understanding Ability - Uyun, Fina Ismatul; Buchori, Achmad; Endahwuri, Dhian (JURNAL PENDIDIKAN MATEMATIKA, 2025)
The ability to understand mathematical concepts is very important for students to develop because it can give rise to other mathematical abilities. Therefore, efforts are made to develop it using geogebra-based interactive multimedia. This research aims to find out how effective geogebra-based interactive multimedia is in improving understanding of mathematical concepts. The method in this research is research and development (RnD) with reference to the ADDIE steps. The subjects in this research were 7th-grade junior high school students. The results of this research show that learning GeoGebra-based interactive multimedia on triangles and quadrilaterals is effective in improving the ability to understand mathematical concepts. These results can be seen from the significant regression value, namely the Sig value. 0.007 < 0.05, so it can be said that there is an influence between the ability to understand mathematical concepts of students who are taught using Geogebra-based interactive multimedia learning in the experimental class is better than the ability to understand mathematical concepts of students who are taught with conventional learning (PBL) in the control class. Keywords: Multimedia, Geogebra, Concept mathematical